2019
DOI: 10.1039/c9sm01313j
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of nanoparticles within a semidilute polyelectrolyte solution

Abstract: We studied the diffusion of charged gold nanoparticles within a semidilute solution of weakly charged polyelectrolyte, polyacrylic acid (PAA) of high molecular weight (Mw = 106 g mol−1) by using fluorescence correlation spectroscopy (FCS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…When it comes to bio‐sensing and drug‐delivery applications, the bulk properties of PEM films play a significant role in their optimal functionality. [ 27–36 ] Various bio‐molecules such as proteins, DNA, RNA can be integrated into the PEM stack via electrostatic interactions or other secondary interactions like hydrogen bonding, charge transfer interactions, chiral recognition, π – π interactions, and covalent bonding (click chemistry reactions). [ 9,37,46–50,38–45 ] Understanding the diffusion kinetics across a PEM stack is a major factor to be considered for employing them for biomolecular loading and release.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to bio‐sensing and drug‐delivery applications, the bulk properties of PEM films play a significant role in their optimal functionality. [ 27–36 ] Various bio‐molecules such as proteins, DNA, RNA can be integrated into the PEM stack via electrostatic interactions or other secondary interactions like hydrogen bonding, charge transfer interactions, chiral recognition, π – π interactions, and covalent bonding (click chemistry reactions). [ 9,37,46–50,38–45 ] Understanding the diffusion kinetics across a PEM stack is a major factor to be considered for employing them for biomolecular loading and release.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies considered translational diffusion of electrostatically stabilized nanoparticles in model polyelectrolyte solutions. Senanayake and co-authors ( 27 ) studied translational diffusion of electrostatically stabilized anionic tannic acid–coated gold nanoparticles (sizes of 5, 20, and 40 nm) in polyacrylic acid (1000 kDa) solutions in distilled water (no salt). The authors reported polymer correlation lengths of 34 to 69 nm; therefore, their studies considered regimes where the particles are smaller or approximately the same size as the polymer correlation length.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these nanoparticle diffusion studies have been done using flexible, neutral polymers or moderately flexible polymers like DNA ( 26 ). Comparatively fewer studies have been performed using polyelectrolyte solutions ( 20 , 27 , 28 ). Models based on obstruction effects, hydrodynamic theories, free volume theory, and length scale–dependent viscosity have been proposed to explain deviations from the Stokes-Einstein equation for nanoparticles undergoing diffusion in complex liquids ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed chemical potential is verified further by developing a mass diffusion coefficient using both approaches, the standard chemical potential of mixing and that of dispersion. The behaviour of the diffusion coefficient is also explained in [78] by a meanfield hydrodynamic theory in porous medium. Interestingly, this seems to coincide with the porous-like model we used in our work, which lead finally to expression Eq.…”
Section: Discussionmentioning
confidence: 99%